Needs, diversity, and urbanicity: An exploration of community factors' relationships to homeless services - Huang, Xi; Sullivan, Andrew (Cities, 2024)
Homeless services play a critical role in addressing homelessness in the United States. Research has shown that unaffordable housing costs and poverty in a community are key predictors of homelessness. Yet, nonprofit organizations and social service providers also respond to other community factors such as diversity and urban setting. However, there is little research on the distribution of services and whether they overlap with the geographic distribution of community needs, housing needs, community diversity, and urbanicity, which undermines our understanding of the linkage between social services and communities and ability to tailor services to specific communities and populations. Thus, this paper aims to explore the distribution of homeless services, particularly their relations to common predictors of homelessness, and the extent to which these relationships vary by service types. By linking HUD's housing-inventory-count dataset with the 5-year samples of the American Community Surveys and using the zip code as the geographic unit, we found that housing needs in a community have a persistently strong relationship with the presence of services, even after controlling for other community characteristics. Additionally, while most zip codes with services are in central cities, suburbs also have a sizeable share of services. •Only 19% of zip codes have any homeless service provider•Housing needs have a strong relationship with the presence of services, even after controlling for community characteristics•The type of homeless service provider does not relate with community characteristics